Earth to moon ebook A memoir. - Zappa, Moon Unit (2024)
From Moon Unit Zappa, the daughter of musical visionary Frank Zappa, comes a memoir of growing up in her unconventional household in 1970s Los Angeles, coming of age in the Hollywood Hills in the 1980s as the "Valley Girl," gaining momentum as an accidental VJ on a new network called MTV, and finding herself after losing her father, then her mother, and the testing of her most important relationships. How can you navigate life as the "normal" child of an extraordinary creative? What is it like to live in a hothouse of individuality that on one hand fosters freedom of expression, and on the other tamps down the basic desires of a child for boundaries and affection? Should you call your parents Frank and Gail from birth? For Moon Unit Zappa, processing a life so punctuated by the whims of genius, the tastes of popular culture, the calculus of celebrity, and the nature of love, was at times eviscerating, at times illuminating—but mostly deeply confusing. Yes, this is a book about growing up in the shadow of Frank Zappa. Moon and her family were a source of constant curiosity, for their unique names and for their father's reputation as a musical savant and fierce protector of the First Amendment, even though he was never a commercial success. Searching for her own path, first as her father's inadvertent musical collaborator and public sidekick with their surprise mega radio hit, then as an actress, an artist, a spiritual person, a wife and mother, Moon Unit calculates ever-changing equations of fame, family, death and ultimately legacy when dealt the shocking news that Gail's will established an unequal distribution among the remaining, tight-knit Zappas, catalyzing a quest for meaning and redemption. With love, humor, and humility, Earth to Moon reminds us that every family is faced with problems that are unique to their particular makeup, but the journey to growing into yourself with grace is as universal as it gets.